Hasan Hanafi's Anthropocentric Theological Approach in Interpreting the Qur‘an - Solehudin, Solehudin (Jurusan Aqidah dan Filsafat Islam Universitas Negri Sunan Gunung Djati Bandung, 2024)
Theological exegesis from classical to medieval times predominantly reflects a theocentric (allahūt) approach, which often limits the functional role of the Quran as hudan li an-nas (guidance for humanity). This traditional interpretation places divine attributes at the centre, sometimes overlooking the Qur an’s direct address to humans. In response, Hasan Hanafi introduced Anthropocentric Theology, a paradigm that seeks to activate theological texts for real-world applications. This study explores Hanafi’s anthropocentric interpretive framework and its implications for contemporary Qur anic exegesis. Using a qualitative descriptive-analytic method, this research is based on library research, analysing primary sources such as Min al-‘Aqidah ila as-Saurah, ad-Din wa as-Saurah, and Qadhaya al-Mu‘asirah, along with secondary literature that supports the discussion. This study applies theo-centric and anthropocentric theories to selected Quranic verses, aligning them with Hanafi’s interpretative structure. The findings show that Anthropocentric Theology serves as both a critique of theocentric interpretations and a new interpretive direction focusing on human agency. This approach emphasizes six key dimensions: (1) Anthropocentrism (at-tarkiz 'ala an-nās), (2) Historical Context (Tarikh nuzūl al-ayāt), (3) Rationality (Ta'aquli), (4) Emancipation (al-musawat fi al-huqūq), (5) Contextualization (at-tafsir bi'tibari as-siyaq), and (6) Social Transformation (at-taqhayur al-ijtima'i). The study concludes that Quranic interpretation must shift from the passive acceptance of fate (taqdīr) to active engagement (ikhtiār), promoting justice, prosperity, and societal reform. By applying eclectic thematic interpretation, anthropocentric theology offers a transformative vision, shifting conditions from corruption to righteousness, oppression to justice, and poverty to prosperity, ensuring the Quran’s continued relevance in modern sociopolitical contexts